2018
DOI: 10.1186/s13068-018-1218-5
|View full text |Cite
|
Sign up to set email alerts
|

Lavender- and lavandin-distilled straws: an untapped feedstock with great potential for the production of high-added value compounds and fungal enzymes

Abstract: BackgroundLavender (Lavandula angustifolia) and lavandin (a sterile hybrid of L. angustifolia × L. latifolia) essential oils are among those most commonly used in the world for various industrial purposes, including perfumes, pharmaceuticals and cosmetics. The solid residues from aromatic plant distillation such as lavender- and lavandin-distilled straws are generally considered as wastes, and consequently either left in the fields or burnt. However, lavender- and lavandin-distilled straws are a potentially re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 46 publications
2
17
0
1
Order By: Relevance
“…So far, various lignocellulosic materials, mainly constituting wastes of arable crops, have been used for the production of fungal laccases. For example, lavender straw [51], wheat bran [52], orange peel [53], and sesame oil cake [54] have been utilized as substrates for laccase production by Pycnoporus cinnabarinus, Cyathus bulleri, Trametes polyzona, and Pleurotus sp., respectively. In the presented study, extracts of grass hay, rapeseed oil cake, and litter of leaves collected in an urban park in autumn were used to prepare an alternative medium for laccase production.…”
Section: Optimization Of the Laccase Productionmentioning
confidence: 99%
“…So far, various lignocellulosic materials, mainly constituting wastes of arable crops, have been used for the production of fungal laccases. For example, lavender straw [51], wheat bran [52], orange peel [53], and sesame oil cake [54] have been utilized as substrates for laccase production by Pycnoporus cinnabarinus, Cyathus bulleri, Trametes polyzona, and Pleurotus sp., respectively. In the presented study, extracts of grass hay, rapeseed oil cake, and litter of leaves collected in an urban park in autumn were used to prepare an alternative medium for laccase production.…”
Section: Optimization Of the Laccase Productionmentioning
confidence: 99%
“…The analysis of reference literature revealed that there are many studies showing the potential of waste rose flower and lavender straw biomass as raw materials for aroma and polysaccharides extraction, for recovery of biologically active substances and their application in the food industry and medicine [ 1 , 29 ]. Lavender distilled straw separately or in combination with other lignocellulose substrates was studied by Ratiarisoa et al [ 30 ] and was successfully recycled as a bio - aggregate for building materials using metakaolin as a binder.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of the antioxidant activity results from its parent cultivars for a direct comparison as well as an inability to rule out the effects of environmental conditions have prevented the delivery of such conclusion. Moreover, according to the previous studies, not all the hybrid species have better antioxidant activity than their parent species. Further study is needed to understand the resulting effects of the interspecific hybridization in Lavandula plants on their antioxidant activity.…”
Section: Resultsmentioning
confidence: 90%